Tous contre le VIH-SIDA (2002-2005): Évaluation de la 1ère phase du Programme de lutte contre le VIH/SIDA de l’Église Evangélique Luthérienne du Cameroun - Rosnes, Ellen Vea; Kristensen, Kåre; Fanta, Christine (Centre for Intercultural Communication, 2006)
All Against AIDS (PLS) started in September 2002, and is coordinated by the Evangelical Lutheran Church in Cameroon (EELC). The project is mainly financed by the Norwegian Agency for Development Cooperation (Norad). From 2003 the Norwegian Missionary Society (NMS) have been responsible for the project and the Centre for Intercultural Communication (SIK) ensure the monitoring.
Free